Legal Analysis of Agency Agreements under the Principle of Taisir in Islamic Contract Law - Annisaul Maslamah; Alamsyah Nurrahmad Putra (Indonesian Journal of Law and Syariah, 2025)
This research aims to analyze agency agreements from the perspective of the principle of taisir (ease), which is one of the fundamental principles that must be upheld in the implementation of contracts within the framework of Sharia. This research employs a normative legal methodology by utilizing library research for data collection. The approaches adopted in this study are the statutory approach and the conceptual approach. The results of this study indicate that the concept of agency in business relationships is a necessity in the process of distributing goods from producers to consumers. There exists a gap in time, geography, and quantity between producers and consumers, which makes the role of agency increasingly indispensable. The agency concept is equated with the relationship between the principal and the agent under the Civil Code (KUH Perdata), and in Sharia contract law, the characteristics of agency can be likened to wakalah al-muqayadah. The existence of agency agreements represents an efficient form of economic behavior, which is also aligned with the principle of taisir in Sharia contracts, defined as the facilitation of daily economic transactions. On the other hand, this also reflects the flexibility of Islamic Sharia in addressing contemporary issues.